ISOLASI DAN IDENTIFIKASI SENYAWA ALKALOID YANG TERKANDUNG DALAM HERBA KOMFREY (Symphytum officinale L.) ASAL TANA TORAJA - Rustiah, Wa Ode (Teknosains: Media Informasi Sains dan Teknologi, 2014)
Has done research on the isolation and identification of compounds alkaloids contained in the komfrey (Symphytum officinale L.) from Toraja. The aim of this research is to determine alkaloid contained in komfrey with infra red spectrophotometry the results from two dimensional thin layer Chromatography a fraction using silica gel GF254 stationary phase and mobile phase chloroform: methanol (8:2) form a blue color staining with Rf value of 0.82 and a positive result is suspected alkaloids. From the results of identification using infrared spectroscopy, results show komfrey suspected to contain alkaloid compounds. mean 0,81 %.